If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = 14x + 4 Reorder the terms: -2 + 2x = 14x + 4 Reorder the terms: -2 + 2x = 4 + 14x Solving -2 + 2x = 4 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -2 + 2x + -14x = 4 + 14x + -14x Combine like terms: 2x + -14x = -12x -2 + -12x = 4 + 14x + -14x Combine like terms: 14x + -14x = 0 -2 + -12x = 4 + 0 -2 + -12x = 4 Add '2' to each side of the equation. -2 + 2 + -12x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -12x = 4 + 2 -12x = 4 + 2 Combine like terms: 4 + 2 = 6 -12x = 6 Divide each side by '-12'. x = -0.5 Simplifying x = -0.5
| 3(c-1)=7 | | X+7-4=-2x+5x+1 | | 17-9m-m=23 | | 5(4m+5)=12 | | 8x^2+1=9x | | 9(11-k)=9(k-5) | | -4-4=3v | | .6x+.133333x+.05x=94 | | 2a+3=180 | | (-2)/(1/2) | | 0.7(n+0.7)=1.4(n-0.4) | | -95=-5(p+9) | | 3(2x+2)=10x+1+-4x+5 | | 2x+p=m-3x | | 2m+5=4m-7 | | 6(h-4)=6h+4 | | 3(x-2)=-18 | | 7-2(6z+8)=-9(z+6)+3 | | 1.6h-72=-4h-30 | | 30=x+3 | | 5y+2=4y+10 | | 3-4=2x+5 | | 3-6(-7y-4)=(-4y+8)-7 | | 3-4=2x-5 | | 4x+2-5y=7-6y | | .5n+5=3 | | 50.00+12.00s= | | c/3+c/6 | | 7(x+9)=7x-9 | | 80=9/5c+32 | | 3m+1=16 | | q=2p+8*p |